Integrating Toontastic into Reading Lessons: A Descriptive Study of Students’ Engagement and Comprehension in Senior High School - Rahayu, Sri; Upa, Rahmawati; Paldy; Hafirah Patang (Universitas Islam Negeri Palopo, 2025)
This research explores the integration of Toontastic, a digital storytelling application, into reading lessons to enhance students’ engagement and reading comprehension in aSenior high school (SMA) setting. The obejective of this research is to find out how the integration of Toontastic into reading lessons influence students’ engagement and reading comprehension in Senior High School. Employing a qualitative descriptive method, the research involved classroom observations, student interviews, and analysis of digital storytelling products created by 24 eighth-grade students over a four-week period. The findings reveal that Toontastic significantly improved students’ behavioral, emotional, and cognitive engagement. Learners actively participated in story construction, expressed enthusiasm, and demonstrated deep interaction with the reading materials. Furthermore, students’ digital stories indicated improved comprehension of narrative texts, including accurate retelling, interpretation, and vocabulary use. The research highlights the value of digital storytelling as a learner centered approach that supports both engagement and textual understanding. It concludes with practical recommendations for educators and suggestions for further research, particularly in integrating technology into literacy instruction. This research contributes to the growing field of interactive media in education by providing insights into how digital tools like Toontastic can transform conventional reading practices.